Kajapati Kulapati கஜபதி குலபதி களிச்சா குளிச்சா - Ashok Rajagopalan,Jeeva Raghunath (Tulika Publishers, 2020)
Story about an elephant; for children.
Children's story. - Translated from English
Keywords: Elephants; Juvenile fiction.; Children's stories; Indic (English); Translations into Tamil.